Educational equity in England: the shortcomings of the UK Government’s COVID-19 response [version 2; peer review: 2 approved] - Sean Kippin (Routledge Open Research)
The UK Government sought to respond to lockdowns and lost learning during the coronavirus disease (COVID-19) pandemic in multiple ways, including replacing cancelled examinations and compensating for lost learning through a National Tutoring Programme. In the case of the former, the system failed to realise the demands of equity by privileging wealthier students and beating a path back to a flawed ‘normality.’ In the case of the latter, while the idea of providing targeted, high quality small group and one on one tutoring to the most in-need students was well-conceived, implementation was a failure - particularly following its contracting out to a large outsourcing company. These two cases demonstrate that English education policy is adherent to a neoliberal conception of education equity, and that attempts to address inequalities are constrained, backfire, or both.